2012
DOI: 10.1152/ajprenal.00678.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of αENaC expression and ENaC activity following blockade of the circadian clock-regulatory kinases CK1δ/ε

Abstract: Increasing evidence suggests that the circadian clock plays an important role in the control of renal function and blood pressure. We previously showed that the circadian clock protein Period (Per)1, positively regulates the expression of the rate limiting subunit of the renal epithelial sodium channel (αENaC), which contributes to blood pressure regulation. Casein kinases 1δ and 1ε (CK1δ/ε) are critical regulators of clock proteins. CK1δ/ε must phosphorylate the circadian clock protein Per1 in order for the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 48 publications
5
48
0
Order By: Relevance
“…Casein kinase (CK)1-␦/ε inhibitor experiments were performed as previously described (30,31). For dose and time course, NCI-H295R cells were treated with either 0.1, 1, 10, or 100 M of the CK1-␦/ε inhibitor PF-670462 or vehicle (water) for 24, 48, or 72 h. For nuclear entry experiments, NCI-H295R cells were treated with 0.1 M PF-670462 or vehicle for 24 h.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Casein kinase (CK)1-␦/ε inhibitor experiments were performed as previously described (30,31). For dose and time course, NCI-H295R cells were treated with either 0.1, 1, 10, or 100 M of the CK1-␦/ε inhibitor PF-670462 or vehicle (water) for 24, 48, or 72 h. For nuclear entry experiments, NCI-H295R cells were treated with 0.1 M PF-670462 or vehicle for 24 h.…”
Section: Animalsmentioning
confidence: 99%
“…Per and Cry dimerize and interact with Clock and Bmal1 to repress their transcriptional activity (3,11). Per1 may not act as a canonical repressor, however, as increasing evidence suggests that Per1 may activate gene expression through an unknown mechanism, and this may occur in a tissue-and gene-specific manner (8,16,18,31,36). However, our recent work (30) demonstrated that this possible mechanism could be through repression of the circadian repressor Cry2.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…7 Our subsequent reports showed that Per1 regulates the expression of the a subunit of the epithelial sodium channel and the activity of epithelial sodium channel. 8,9 Consistent with these mechanistic molecular findings in renal models, studies in circadian KO mice have consistently demonstrated a role for each of the core clock proteins in BP control. [10][11][12][13] An important role for the kidney in these BP phenotypes has often been proposed, but the lack of renal cell type-specific KO models of circadian genes has prevented the use of a genetic model to directly test this hypothesis.…”
mentioning
confidence: 68%
“…9 The Folic Acid for Vascular Outcomes Reduction in Transplantation trial failed to show a benefit of folic acid therapy on CV events in 4110 kidney transplant recipients. However, it generated a large dataset of carefully phenotyped transplant recipients, with follow-up and validated endpoints, which the investigators have used to study the role of BP on CVD.…”
Section: Nonementioning
confidence: 99%